Political and Economic Dimensions of the Dominance of Selected Asian Recycling Yards in the World - Małgorzata Kamola-Cieślik (Polish Political Science Yearbook)
India, Bangladesh, and Pakistan have dominated the global ship recycling market in the 21st century. A recycled ship provides steel and other metals for industrial reuse. In addition to economic gains, ship recycling affects the environment and workers’ health. The article compares the changes in the policies of the governments of India, Bangladesh, and Pakistan regarding recycling shipyard operations from 2009-2022 in the context of international and EU law standards. It also shows the impact of international organizations, shipbuilding trade unions, Shipbreaking Platform non-governmental, Maersk shipping company, and Norway on the decisions of South Asian countries to make them ratify the Hong Kong International Convention for the Safe and Environmentally Sound Recycling of Ships. Analysis of the collected research material allows us to conclude that the governments of India, Bangladesh, and Pakistan have shown varying degrees of understanding of introducing legal regulations for safe ship recycling.